The role of orographic effects on occurrence of the heavy rainfall event over Central Vietnam in November 1999 - Nhu, Dang Hong; Anh, Nguyen Xuan; Phong, Nguyen Binh; Quang, Nguyen Dang; Nguyen, Hiep Van (Vietnam Journal of Marine Science and Technology, 2017)
In this study, the WRF model is used to investigate the role of Central Vietnam terrain on occurrence of the heavy rainfall event in November 1999 over Central Vietnam. Two model experiments with and without terrain were performed to examine the orographic blocking effects during the event. In the terrain experiment, the results from a three-day simulation show that the model reasonably well captures northeast monsoon circulation, tropical cyclones and the occurrence of heavy rainfall in Central Vietnam. The topography causes a high pressure anomaly intensifying northeast monsoon. When the terrain is removed, the three-day accumulated rainfall decreases approximately 75% in comparison with that in the terrain experiment. The terrain blocking and lifting effects in strong wind and moisture laden conditions combined with convergence circulation over open ocean are the main factors for occurrence of the heavy rainfall event